The philosophy in the creation of traditional Malay carving motifs in Peninsula Malaysia - Haziyah Hussin; Zawiyah Baba; Aminuddin Hassan; Aishah@Eshah Mohamed (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
This paper explains how the concept of the creation of Malay woodcarving motifs is associated with the ancient Malay kingdom of Langkasuka which came under the influence of Hinduism. However, since the coming of Islam, the philosophy of creating Malay carving motifs had undergone discernable changes. The motifs created have been found to be adapted to avoid contravening Islamic principles and values. Generally, the creation of traditional Malay carving motifs has its own guiding principles which differentiate it from carving traditions elsewhere. Basically, traditional Malay carving motifs can be categorised into decorative motifs or patterns which have been inspired by early or ancient Malay motifs such as the design pattern with floral motifs, stalks of leaves and tendrils (awang larat which literally means meandering clouds) which are found in the environment of Malay society as well as motifs inspired by the imagination of early carvers. This paper concludes with an explanation on the philosophy of selecting traditional Malay wood carving motifs based on Malay carving techniques.